Activated carbon synthesis from durian peel for ammonium ion adsorption - Minh Tien Pham; Thi Kim Yen Truong; Thi Kim Tho Truong; Thanh Phu Le; Thi Bich Quyen Tran; Huynh Vu Thanh Luong (CTU Journal of Innovation and Sustainable Development)
In this study, activated carbon (AC) used as a high-efficiency and low-cost for ammonium ion (NH4+) adsorbent was synthesized, for the first time from durian peel by a one-step chemical activation process using phosphoric acid. The effects of pH, contact time, initial concentration, and adsorbent dose on the NH4+ adsorption in aqueous solution were investigated in detail. The as-synthesized AC was characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller method (BET). As a result, AC from durian peel was successfully synthesized at a calcination temperature of 600oC, phosphoric acid concentration of 20% and an activation temperature of 50℃. The optimal condition for the NH4+ adsorption in aqueous solution was at pH 7.0, adsorption time of 60 min., initial concentration of 40 mg/L, with an adsorbent mass of 0.1 g. The adsorption kinetics and adsorption isotherm of NH4+ adsorption process showed that the adsorption process was fitted to pseudo-second-order kinetic model and Freundlich adsorption isotherm, indicating a physical and multilayer adsorption process. In general, this study provides an efficient, cost-effective adsorbent for NH4+ removal from aqueous solution.